2023
DOI: 10.1007/s00784-023-04883-w
|View full text |Cite
|
Sign up to set email alerts
|

Wear behavior at margins of direct composite with CAD/CAM composite and enamel

Abstract: Objectives The aim was to investigate the two-body wear at the marginal area between direct filling composites and substrate of CAD/CAM composites or enamel. Materials and methods Flat specimens were prepared from CAD/CAM composites (CERASMART 270 and SFRC CAD) and bovine enamel. A box-shaped cavity cut into CAD/CAM composites and enamel surfaces was made. The prepared cavity in CAD/CAM composites was treated with a primer, while in enamel, the cavity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Thereby, microfibres filler loading had no negative impact on the colour stability of the SFRC CAD. This finding aligns with prior research that showed favourable surface and optical properties of SFRC CAD when compared to various particulate-filled composites [ 11 , 14 , 16 ]. Within the mentioned research, the microfibres of the SFRC CAD did not protrude from surface after polishing or wear test; instead, they were polished in the resin matrix, resulting in often a uniformly smooth surface.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thereby, microfibres filler loading had no negative impact on the colour stability of the SFRC CAD. This finding aligns with prior research that showed favourable surface and optical properties of SFRC CAD when compared to various particulate-filled composites [ 11 , 14 , 16 ]. Within the mentioned research, the microfibres of the SFRC CAD did not protrude from surface after polishing or wear test; instead, they were polished in the resin matrix, resulting in often a uniformly smooth surface.…”
Section: Discussionsupporting
confidence: 92%
“…To achieve a more acceptable stress distribution between restoration and underlaying tooth structure, some researchers [ 8 , 9 ] advocate using materials having an elastic modulus similar to that of dentin. Due to elastic modulus, wear characteristics, colour integration, and malleability in thin layers, composite-based CAD/CAM materials have become increasingly common over the past 10 years [ 10 , 11 ]. Compared to traditional light-cured resin composites, CAD/CAM composites have significantly higher monomer conversion due to the high temperature and pressure during polymerisation, resulting in composites with superior mechanical properties and biocompatibility [ 2 ].…”
Section: Introductionmentioning
confidence: 99%